An Enriched Information Security Framework from Various Attacks in the IoT (International Journal of Innovative Research in Computer Science & Technology, 2020)
Security in various E-commerce Applications  includes an efficient framework in Information Security  especially in Computer Security, Data Security and other  online transactions in E-commerce applications. Security in  E-Commerce application plays an important role for the  secure and scalable transaction which includes various  dimensions such as security-integrity, Confidentiality, Non repudiation, Privacy etc. Hence for the Security of Online  Transactions in E-Commerce based application various  Security algorithms are implemented. Although these  Security algorithms are efficient and provides Security from  various attacks but Data Storage during the transactions and  Computational time of the algorithms is also important. The  existing architecture proposed for the security of online e transactions in web applications provides security from  different attacks and is efficient in terms of computational  parameters, but there are certain issues which need to be  overcome such as: Security Prevention from different attacks  during Online Transactions in Web Mining especially in E commerce Applications, Increase use of Computational Cost  at the Client and Server Side. The Proposed framework  provides Security prevention from various attacks especially  in IoT. The methodology implemented here works on the  basis of authenticating the validity of the User by allocating  a challenge value and hope that our proposed framework will  be more effective and efficient.
Keywords: Information Security; IoT, Computer Security; E-commerce; Authentication